PROGRESSION AS THE BASIS OF KINEMATIC AND DYNAMIC THEORIES - Kamal , Б.; Koshtybayev, Т.; Dikambay, Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
This article shows that the structural content of kinematic and dynamic theories of mechanical movements is based on the relationships between uniformly varying mechanical quantities according to arithmetic progressions or according to the law of linear functions and the quantities that are responsible for these changes. These relationships are carried out through progression formulas and graphs of the dependence of varying quantities on time and are estimated through the angle of inclination of linear dependencies. If in kinematic theories the law of uniform change of body coordinates and its violation are described by linear and parabolic laws, then in dynamic theories the uniform change of velocities, displacements, momentum, kinetic energy and the work of external forces are considered from the point of view of the law of arithmetic progressions. Mechanical quantities such as the acceleration received by the body from external forces, external actions, the power of actions, the average power of actions is represented as the speed of progressions.